Fire extinguishing agent for extinguishing A-type B-type and lithium battery fire disasters and preparation method of fire extinguishing agent

By using the composite technology of fire extinguishing microcapsules and aerogels in the fire extinguishing agent, the problem of failure of existing fire extinguishing agents at high temperatures and adhesion of non-planar positions is solved, and a more efficient and lasting fire extinguishing effect is achieved.

CN119455317AActive Publication Date: 2025-02-18JIANGSU JIATAI FIRE TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411515735.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing fire extinguishing agent fails at high temperatures and cannot effectively extinguish lithium battery fires. It is difficult to adhere to fires in non-planar locations, affecting fire extinguishing efficiency.

Method used

The composite technology of fire-extinguishing microcapsules and aerogels is adopted. The microcapsules are wrapped in perfluorohexanone. The shell material uses polyethylene terephthalate modified by alumina nanoparticles. The aerogel is a silicon-based aerogel. The aerogel is evenly attached to the surface of the microcapsule through electrostatic spraying technology.

Benefits of technology

It improves the storage and use stability of fire extinguishing agents, ensures that the fire extinguishing material can be effectively released at high temperatures, and the low density and porous structure of the aerogel allow it to effectively adhere in non-planar positions, enhancing fire extinguishing efficiency and durability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fire extinguishing agents, and particularly provides a fire extinguishing agent for extinguishing A-type B-type and lithium battery fire disasters and a preparation method of the fire extinguishing agent. The fire extinguishing agent comprises a fire extinguishing microcapsule and aerogel. According to the fire extinguishing agent with the fire extinguishing microcapsules and the aerogel as main components, the fire extinguishing material is wrapped in the microcapsule structure, the storage stability and the use stability of the wrapped fire extinguishing material can be improved, the microcapsules can be isolated through the aerogel structure, agglomeration of the microcapsules is avoided, the dispersing performance of the microcapsules can be improved, and the fire extinguishing effect is improved. According to the present invention, the aerogel has characteristics of uniform dispersion during fire extinguishing, good fire extinguishing effect, low density, large specific surface area and good heat insulation effect, can provide good adhesion performance, can be well attached to the fire source position when the lithium battery fire disasters are located at different positions, can isolate the heat at the fire source position, and can provide the good fire extinguishing effect; and the probability of thermal runaway of the lithium battery is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fire extinguishing agents, and in particular to a fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires and a method for configuring the same. Background Art

[0002] With the rapid development of new energy vehicles and lithium battery technology, lithium batteries are widely used as the main energy storage device. However, lithium batteries may experience thermal runaway when charging, discharging or affected by external factors, leading to fire or explosion accidents, which seriously threaten personal safety and property safety. Traditional fire extinguishing agents such as water and foam fire extinguishing agents are effective in extinguishing Class A and Class B fires, but have limited extinguishing effects on lithium battery fires. In addition, conventional fire extinguishing agents often lose their fire extinguishing effect at high temperatures and cannot meet the special fire extinguishing needs of new energy vehicles.

[0003] In view of the characteristics of lithium battery fires, many researchers have begun to explore new fire extinguishing agents. Among them, perfluorinated compounds have attracted attention for their excellent fire extinguishing performance, especially perfluorohexanone, which can quickly reduce the flame temperature and effectively isolate oxygen. However, perfluorohexanone has a low specific heat capacity and limited heat absorption during gasification. It can generally achieve good fire extinguishing effects for Class A or Class B fires. However, when it comes to lithium battery fires, due to the high energy density of lithium batteries, when a lithium battery fire occurs, it is usually accompanied by thermal runaway. A large amount of heat and gas jets will be generated inside the lithium battery, which will weaken the fire extinguishing advantage of perfluorohexanone. Even perfluorohexanone will be pushed away from the fire source during the lithium battery explosion, and perfluorohexanone cannot directly act on the fire source.

[0004] In view of the above-mentioned deficiencies, some existing technologies have adopted different technical solutions, such as forming perfluorohexanone into microcapsules, and utilizing the structural stability of the microcapsules to transport perfluorohexanone to the location of the fire source of the lithium battery or even to the inside, thereby cooling the inside. Some further improved solutions combine microcapsules containing perfluorohexanone with other media such as hydrogels to further increase the upper limit of heat absorption.

[0005] However, hydrogels are difficult to effectively adhere to in some specific scenarios. For example, when the location where fire needs to be extinguished is not flat, hydrogels are more likely to fall off due to their greater density and cannot be effectively attached. This not only directly affects the working efficiency of the hydrogels, but also affects the fire-extinguishing effect of the microcapsules entrained therein. Summary of the invention

[0006] In view of this, the present invention proposes a fire extinguishing agent and a method for its configuration which has a more reasonable design and can be used for both Class A, Class B and lithium battery fires.

[0007] The technical solution of the present invention is implemented as follows: The present invention provides a fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires, and the fire extinguishing agent includes fire extinguishing microcapsules and aerogels.

[0008] In some embodiments, the fire extinguishing microcapsule comprises a core material and a shell, the core material is perfluorohexanone, the shell material is polyethylene terephthalate modified with aluminum oxide nanoparticles, and the core material accounts for 40-50% of the total mass of the microcapsule.

[0009] In some embodiments, the method for preparing the fire extinguishing microcapsules comprises:

[0010] Core material preparation: perfluorohexanone is added dropwise to the stirred aqueous phase to form a core material emulsion with a mass concentration of 40%-50%, and the aqueous phase is a Tween-80 aqueous solution with a mass concentration of 0.5%-2.0%;

[0011] Shell material preparation: dissolve polyethylene terephthalate in ethyl acetate, add aluminum oxide nanoparticles, and stir evenly to obtain a shell material suspension;

[0012] Preparation of microcapsules: add the shell material suspension to the stirring core material emulsion, add glutaraldehyde to carry out cross-linking reaction, then heat to 60-80°C, keep stirring for 2-4 hours, filter, wash and dry to obtain fire-extinguishing microcapsules.

[0013] In some embodiments, during the core material preparation, the stirring speed of the aqueous phase is 5000-10000 rpm.

[0014] In some embodiments, the concentration of polyethylene terephthalate in the shell material suspension is 5%-10%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 30%-40%.

[0015] In some embodiments, the volume ratio of the shell material suspension to the core material emulsion is 1:(1-3).

[0016] In some embodiments, the aerogel is a silicon-based aerogel.

[0017] In some embodiments, the method for preparing the aerogel comprises:

[0018] Preparation of sol: After tetraethyloxysilane and ethanol are mixed and stirred evenly, hydrochloric acid is added to adjust the pH value to 2-3, and water is added at the same time, and the mixture is stirred and reacted for 20-40 minutes to obtain a sol;

[0019] Gel preparation: Add ammonia water to the sol, adjust the pH value to 5-6, stir and react for 12-24 hours, and stand at 30-50°C for 24 hours to obtain a gel;

[0020] Solvent replacement: Soak the gel in ethanol for 12-24 hours, and repeat the above soaking steps 3-5 times;

[0021] Drying: The solvent-replaced gel is immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state, and then the carbon dioxide is slowly released to complete drying to obtain aerogel. The aerogel is crushed to obtain aerogel particles with an average particle size of 10-100μm.

[0022] In some embodiments, the solvent replacement step further comprises adding an aqueous solution of potassium carbonate to the ethanol.

[0023] In a second aspect, the present invention further provides a method for configuring the fire extinguishing agent, comprising the following steps:

[0024] Step 1: Pour the dried aerogel powder into the hopper of the electrostatic spraying equipment, spray the aerogel powder onto the surface of the fire extinguishing microcapsules at an electrostatic voltage of 50-70 kV and an air pressure of 0.1-0.3 MPa, with a spraying distance of 15-30 cm and a spraying time of 3-5 s;

[0025] Step 2: After spraying, the composite material obtained after spraying is dried at 40-60° C. for 12-24 hours to obtain a fire extinguishing agent.

[0026] The mass ratio of fire extinguishing microcapsules to aerogel powder is (2.5-8):1

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention adopts fire extinguishing microcapsules and aerogels as the main components of the fire extinguishing agent. The fire extinguishing material is wrapped in the microcapsule structure, which can improve the storage stability and use stability of the wrapped fire extinguishing material, and effectively avoid the fire extinguishing material being driven by external force to leave the fire source when a Class A or Class B fire occurs in a lithium battery or other special scenarios, resulting in the problem that the fire source cannot be extinguished in time. Secondly, the aerogel structure can isolate the microcapsules to avoid agglomeration of the microcapsules, which helps to improve the dispersion performance of the microcapsules, so that the microcapsules are evenly dispersed during fire extinguishing and achieve a good fire extinguishing effect. Thirdly, the aerogel has a small density, a large specific surface area, and a good thermal insulation effect, and can provide better adhesion performance. When targeting lithium battery fires at different locations, it can better adhere to the fire source location and can isolate the heat at the fire source, effectively reducing the probability of thermal runaway of the lithium battery. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0031] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0032] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0033] Hydrogel has a high density and viscosity. When applied to a non-planar or vertical surface, gravity causes it to easily slide off the surface and it cannot continue to adhere to the fire source, affecting its fire extinguishing efficiency.

[0034] Aerogel is an extremely light material with a very low density, typically hundreds of times lighter than hydrogel. Its low density means that even when applied in a vertical or non-planar position, aerogel particles can effectively adhere to the surface of the fire source, rather than falling due to gravity like hydrogel. This property ensures that the fire extinguishing agent can maintain good stability on complex terrain or structures. The porous structure of aerogel has a strong surface adsorption capacity. Its large specific surface area can be firmly adsorbed on various surfaces. Even if the surface is irregular, aerogel particles can be evenly attached through electrostatic spraying or other means, enhancing the effectiveness of the fire extinguishing agent in non-planar positions.

[0035] The hydrogel is not only easy to fall off, but also affects the adhesion and release effect of the fire extinguishing agent (such as microcapsules) entrained inside it, resulting in the inability to stably release the fire extinguishing agent for a long time, thereby reducing the overall fire extinguishing efficiency.

[0036] The present invention uses a composite technology of aerogel and microcapsules to replace hydrogels, ensuring that the microcapsules can be firmly adhered to the surface of the fire source through the adhesion of the aerogel. The low density, stability and porosity of the aerogel enable it to be effectively attached to various surfaces, avoiding the problem of fire extinguishing agent failure caused by the falling of the hydrogel. Aerogel can not only enhance the adhesion of the microcapsules, but its porous structure can also provide thermal insulation protection for the microcapsules, extend the working time of the microcapsules, and ensure that the fire extinguishing agent (such as perfluorohexanone) can be continuously and stably released around the fire source. Compared with hydrogel, this composite structure of aerogel greatly enhances the durability and fire extinguishing efficiency of the fire extinguishing agent.

[0037] In some further schemes, the shell material also has aluminum oxide nanoparticles. PET is a polymer commonly used in industrial and high-performance products with excellent heat resistance and mechanical strength. As the shell material of the microcapsule, PET can maintain its structural stability under high temperature conditions, prevent the microcapsules from being thermally damaged in the early stage of the fire, and ensure that the fire extinguishing agent can be released at the right time. Adding aluminum oxide nanoparticles to PET can significantly improve its high temperature resistance and resistance to thermal decomposition. Alumina has a very high melting point (about 2072°C), which can enhance the tolerance of microcapsules in high-temperature fire scenarios and prevent the microcapsules from rupturing prematurely. At the same time, the porous structure formed by aluminum oxide nanoparticles in the shell material can further enhance the adhesion of microcapsules on complex surfaces (such as the surface of battery packs), ensuring that the fire extinguishing agent can effectively cover the fire source. Through the high temperature stability of the shell material, the fire extinguishing microcapsules can achieve controlled release, that is, when the fire temperature gradually increases, the shell will slowly decompose, thereby gradually releasing the perfluorohexanone inside. This controlled release mechanism ensures that the fire extinguishing agent will not be exhausted at one time, but will be released according to the temperature change of the fire source, providing a continuous fire extinguishing effect.

[0038] The preparation method of the fire extinguishing microcapsule comprises:

[0039] Core material preparation: perfluorohexanone is added dropwise to the stirred aqueous phase to form a core material emulsion, wherein the aqueous phase is a Tween-80 aqueous solution with a mass concentration of 0.5%-2.0%;

[0040] Shell material preparation: dissolve polyethylene terephthalate in ethyl acetate, add aluminum oxide nanoparticles, and stir evenly to obtain a shell material suspension;

[0041] Preparation of microcapsules: add the shell material suspension to the stirring core material emulsion, add glutaraldehyde to carry out cross-linking reaction, then heat to 60-80°C, keep stirring for 2-4 hours, filter, wash and dry to obtain fire-extinguishing microcapsules.

[0042] By using Tween-80 as a surfactant to form an oil-in-water (O / W) emulsion, perfluorohexanone is evenly dispersed into fine droplets in the aqueous phase to ensure that the core material can be evenly distributed in the microcapsule. 30%-40% by mass of aluminum oxide nanoparticles are added to the PET solution and stirred evenly to form a shell material suspension. Aluminum oxide nanoparticles can improve the high temperature resistance and adhesion of the shell material, making it more stable in high temperature scenarios such as lithium battery fires. The prepared shell material suspension is added dropwise to the stirring core material emulsion. By adding dropwise, it can be ensured that the shell material is evenly coated on the surface of the perfluorohexanone droplets to form a preliminary microcapsule. During the coating process, glutaraldehyde is added as a cross-linking agent to promote the cross-linking reaction between PET molecules, thereby improving the structural strength and stability of the shell material. The cross-linking reaction prevents the shell material from easily breaking at high temperatures and enhances the mechanical properties of the microcapsule. The microcapsule mixture is heated to 60-80°C and stirred for 2-4 hours to ensure that the cross-linking reaction is complete and the shell material is further solidified. This process helps to form a complete and stable microcapsule structure.

[0043] During the core material preparation, the stirring speed of the aqueous phase is 5000-10000 rpm.

[0044] Perfluorohexanone, as the core material, is a hydrophobic substance, while the water phase is a hydrophilic system. In order to ensure that perfluorohexanone can be evenly dispersed in the water phase to form fine droplets, high-speed stirring can provide sufficient shear force to help the oil phase perfluorohexanone form evenly dispersed droplets in the water phase. By adjusting the stirring speed between 5000-10000rpm, the particle size of the oil droplets in the emulsion can be effectively controlled to avoid the agglomeration of large particles of oil droplets. This fine particle size of oil droplets provides better conditions for the subsequent shell material coating, which can ensure that the shell material can be evenly covered on the surface of the core material.

[0045] The concentration of polyethylene terephthalate in the shell material suspension is 5%-10%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 30%-40%.

[0046] The volume ratio of the shell material suspension to the core material emulsion is 1:(1-3).

[0047] It is composed of ethyl acetate, polyethylene terephthalate (PET) and aluminum oxide nanoparticles, which are mainly responsible for forming the shell of the microcapsule, ensuring its heat resistance, mechanical strength and controlled release performance. Perfluorohexanone (fire extinguishing agent) is dispersed in Tween-80 aqueous solution to form a stable emulsion, which is mainly used to provide the core material of the fire extinguishing agent. By adjusting the volume ratio of the shell material suspension and the core material emulsion, the precise control of the microcapsule structure can be achieved through the speed of dripping the shell material suspension and the stirring intensity. The adjustment of the volume ratio is the key to the optimization of the microcapsule performance, which determines its shell material thickness, core material content and the final fire extinguishing agent release characteristics. The design of a shell material suspension to core material emulsion volume ratio of 1: (1-3) provides flexible microcapsule structure adjustment options, allowing the fire extinguishing agent to adapt to different fire types and scenarios. By controlling the volume ratio, the shell material thickness, core material content and release rate of the microcapsule can be balanced to ensure that the fire extinguishing agent exhibits the advantages of long-term protection, rapid response or balanced performance in different scenarios. This design provides a more adaptable and efficient solution for microcapsule fire extinguishing agents in dealing with complex fires (such as lithium battery fires).

[0048] The aerogel is a silicon-based aerogel.

[0049] The preparation method of the aerogel comprises:

[0050] Preparation of sol: After tetraethyloxysilane and ethanol are mixed and stirred evenly, hydrochloric acid is added to adjust the pH value to 2-3, and water is added at the same time, and the mixture is stirred and reacted for 20-40 minutes to obtain a sol;

[0051] Gel preparation: Add ammonia water to the sol, adjust the pH value to 5-6, stir and react for 12-24 hours, and stand at 30-50°C for 24 hours to obtain a gel;

[0052] Solvent replacement: Soak the gel in ethanol for 12-24 hours, and repeat the above soaking steps 3-5 times;

[0053] Drying: The solvent-replaced gel is immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state, and then the carbon dioxide is slowly released to complete drying to obtain aerogel. The aerogel is crushed to obtain aerogel particles with an average particle size of 10-100μm.

[0054] The solvent replacement step further includes adding an aqueous solution of potassium carbonate to the ethanol.

[0055] Potassium carbonate can absorb a large amount of heat through phase change under high temperature conditions. Its heat absorption process helps to quickly reduce the temperature in the fire source environment, thereby inhibiting the spread of the fire. At higher temperatures, potassium carbonate can also undergo decomposition reactions to further absorb heat. During the solvent replacement process of the aerosol, potassium carbonate in water is gradually introduced into ethanol, and then potassium carbonate is introduced into the pore structure of the aerogel through the ethanol carrier. The potassium carbonate solution can fully penetrate into the porous structure of the aerogel, ensuring that potassium carbonate is evenly distributed inside and on the surface of the aerogel to form a composite material. This uniform distribution can maximize the heat absorption effect of potassium carbonate and respond quickly when a fire occurs.

[0056] By introducing potassium carbonate into the porous structure of aerogel, the composite material can not only isolate the external heat source through the low thermal conductivity of aerogel, but also achieve multi-level cooling of the inner and outer layers through the phase change heat absorption process of potassium carbonate, thereby achieving a better cooling effect in the fire source environment. The addition of potassium carbonate improves the heat absorption capacity of aerogel, enabling it to better adapt to high temperature and high energy density fire scenes, such as lithium battery fires. When faced with severe thermal runaway, the material can effectively curb the spread of fire by rapidly absorbing heat.

[0057] The method for preparing a fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires comprises the following steps:

[0058] Step 1: Pour the dried aerogel powder into the hopper of the electrostatic spraying equipment, spray the aerogel powder onto the surface of the fire extinguishing microcapsules at an electrostatic voltage of 50-70 kV and an air pressure of 0.1-0.3 MPa, with a spraying distance of 15-30 cm and a spraying time of 3-5 s;

[0059] Step 2: After spraying, the composite material obtained after spraying is dried at 40-60° C. for 12-24 hours to obtain a fire extinguishing agent.

[0060] Electrostatic spraying can make the charged aerogel powder evenly adhere to the surface of the microcapsule through the principle of electrostatic adsorption, forming a stable aerogel coating. This coating can not only enhance the thermal insulation performance of the microcapsule, but also improve its overall heat absorption efficiency. The ultra-low thermal conductivity and porous structure of aerogel enable it to effectively block the heat transfer of the fire source, and the microcapsule composite material with the addition of aerogel can provide more effective protection in the fire environment, especially in high-temperature scenarios such as lithium battery fires, and has a significant cooling effect. Low-temperature drying can prevent the microcapsule structure from being damaged, while maintaining the integrity of the aerogel and avoiding secondary decomposition at high temperatures.

[0061] Example 1

[0062] Preparation of fire extinguishing microcapsules:

[0063] Perfluorohexanone was added dropwise to the aqueous phase at a stirring speed of 8000 rpm to form a core material emulsion with a mass concentration of 45%, and the aqueous phase was a Tween-80 aqueous solution with a mass concentration of 1%;

[0064] Dissolving polyethylene terephthalate in ethyl acetate, adding aluminum oxide nanoparticles with an average particle size of 50 nm, and stirring evenly to obtain a shell material suspension, wherein the concentration of polyethylene terephthalate in the shell material suspension is 8%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 35%;

[0065] The shell material suspension was added dropwise to the core material emulsion at a stirring speed of 8000 rpm. After the addition was completed, glutaraldehyde was added under stirring for cross-linking reaction. The mixture was then heated to 70°C and stirred for 3 hours. The mixture was filtered, washed and dried to obtain fire-extinguishing microcapsules. The volume ratio of the shell material suspension to the core material emulsion was 1:2.

[0066] Silicon-based aerogel preparation:

[0067] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0068] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0069] Soak the gel in ethanol for 18 h, and repeat the above soaking steps 4 times;

[0070] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0071] Preparation of fire extinguishing agent:

[0072] 100 g of dried aerogel particles were poured into the hopper of the electrostatic spraying equipment, and the aerogel powder was sprayed onto the surface of 500 g of fire extinguishing microcapsules at an electrostatic voltage of 60 kV and an air pressure of 0.2 MPa. The spraying distance was 20 cm, the spraying angle was 90°, and the spraying time was 4 s. During the spraying process, the microcapsules were stirred at 100 rpm. After the spraying was completed, the composite material obtained after spraying was dried at 50°C for 20 hours to obtain a fire extinguishing agent.

[0073] Example 2

[0074] Preparation of fire extinguishing microcapsules:

[0075] Perfluorohexanone was added dropwise to the aqueous phase at a stirring speed of 5000 rpm to form a core material emulsion with a mass concentration of 40%, and the aqueous phase was a Tween-80 aqueous solution with a mass concentration of 0.5%;

[0076] Dissolving polyethylene terephthalate in ethyl acetate, adding aluminum oxide nanoparticles with an average particle size of 50 nm, and stirring evenly to obtain a shell material suspension, wherein the concentration of polyethylene terephthalate in the shell material suspension is 5%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 30%;

[0077] The shell material suspension was added dropwise to the core material emulsion at a stirring speed of 5000 rpm. After the addition was completed, glutaraldehyde was added under stirring for cross-linking reaction. The mixture was then heated to 60°C and stirred for 4 hours. The mixture was filtered, washed and dried to obtain fire-extinguishing microcapsules. The volume ratio of the shell material suspension to the core material emulsion was 1:3.

[0078] Silicon-based aerogel preparation:

[0079] Tetraethyloxysilane and ethanol were mixed and stirred in a mass ratio of 1:3, and then hydrochloric acid was added to adjust the pH value to 2.9. At the same time, water 3 times the volume of tetraethyloxysilane was added, and the mixture was stirred and reacted for 40 minutes to obtain a sol.

[0080] Ammonia water was added to the sol to adjust the pH value to 5.0, and the reaction was stirred for 20 h, and then allowed to stand at 30°C for 18 h to obtain a gel;

[0081] Soak the gel in ethanol for 12 h, and repeat the above soaking steps 5 times;

[0082] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0083] Preparation of fire extinguishing agent:

[0084] 100 g of dried aerogel particles were poured into the hopper of the electrostatic spraying equipment, and the aerogel powder was sprayed onto the surface of 250 g of fire extinguishing microcapsules at an electrostatic voltage of 70 kV and an air pressure of 0.1 MPa. The spraying distance was 15 cm, the spraying angle was 90°, and the spraying time was 3 s. During the spraying process, the microcapsules were stirred at 100 rpm. After the spraying was completed, the composite material obtained after spraying was dried at 40°C for 24 hours to obtain a fire extinguishing agent.

[0085] Example 3

[0086] Preparation of fire extinguishing microcapsules:

[0087] Perfluorohexanone was added dropwise to the aqueous phase at a stirring speed of 10000 rpm to form a core material emulsion with a mass concentration of 40%, and the aqueous phase was a Tween-80 aqueous solution with a mass concentration of 2%;

[0088] Dissolving polyethylene terephthalate in ethyl acetate, adding aluminum oxide nanoparticles with an average particle size of 50 nm, and stirring evenly to obtain a shell material suspension, wherein the concentration of polyethylene terephthalate in the shell material suspension is 10%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 40%;

[0089] The shell material suspension was added dropwise to the core material emulsion at a stirring speed of 10000 rpm. After the addition was completed, glutaraldehyde was added under stirring for cross-linking reaction. The mixture was then heated to 80°C and stirred for 2 hours. The mixture was filtered, washed and dried to obtain fire-extinguishing microcapsules. The volume ratio of the shell material suspension to the core material emulsion was 1:1.

[0090] Silicon-based aerogel preparation:

[0091] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:5, and then hydrochloric acid was added to adjust the pH value to 2.0. At the same time, water 4 times the volume of tetraethyloxysilane was added, and the mixture was stirred and reacted for 40 minutes to obtain a sol.

[0092] Ammonia water was added to the sol to adjust the pH value to 6.0, and the reaction was stirred for 12 h, and then allowed to stand at 50° C. for 12 h to obtain a gel;

[0093] Soak the gel in ethanol for 24 h, and repeat the above soaking step 3 times;

[0094] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0095] Preparation of fire extinguishing agent:

[0096] 100 g of dried aerogel particles were poured into the hopper of the electrostatic spraying equipment, and the aerogel powder was sprayed onto the surface of 800 g of fire extinguishing microcapsules at an electrostatic voltage of 50 kV and an air pressure of 0.3 MPa. The spraying distance was 30 cm, the spraying angle was 90°, and the spraying time was 5 s. During the spraying process, the microcapsules were stirred at 100 rpm. After the spraying was completed, the composite material obtained after spraying was dried at 60°C for 12 h to obtain a fire extinguishing agent.

[0097] Example 4

[0098] On the basis of Example 1, keeping other conditions unchanged, the method for preparing the fire extinguishing agent is to stir and mix 500 g of the fire extinguishing microcapsules and 100 g of the dry aerogel powder at a rotation speed of 100 rpm for 10 seconds to obtain the fire extinguishing agent.

[0099] Example 5

[0100] On the basis of Example 1, keeping other conditions unchanged, the preparation method of silicon-based aerogel is as follows:

[0101] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0102] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0103] The gel was immersed in an ethanol solution for 18 hours, wherein the ethanol solution was prepared by mixing a 10 wt % potassium carbonate aqueous solution with ethanol in a volume ratio of 1:2. The above immersion step was repeated 4 times;

[0104] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0105] Example 6

[0106] On the basis of Example 1, keeping other conditions unchanged, the preparation method of silicon-based aerogel is as follows:

[0107] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0108] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0109] The gel was immersed in an ethanol solution for 18 hours, wherein the ethanol solution was prepared by mixing a 10 wt % potassium carbonate aqueous solution with ethanol in a volume ratio of 1:2. The above immersion step was repeated 4 times;

[0110] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0111] The fire extinguishing agent is prepared by stirring and mixing 500 g of fire extinguishing microcapsules and 100 g of dry aerogel powder at a rotation speed of 100 rpm for 10 seconds to obtain the fire extinguishing agent.

[0112] Example 7

[0113] On the basis of Example 1, keeping other conditions unchanged, the preparation method of silicon-based aerogel is as follows:

[0114] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0115] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0116] The gel was immersed in an ethanol solution for 18 hours, wherein the ethanol solution was prepared by mixing a 10 wt % potassium carbonate aqueous solution with ethanol in a volume ratio of 1:2. The above immersion step was repeated 4 times;

[0117] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0118] Comparative Example 1

[0119] Preparation of fire extinguishing microcapsules:

[0120] Perfluorohexanone was added dropwise to the aqueous phase at a stirring speed of 8000 rpm to form a core material emulsion with a mass concentration of 45%, and the aqueous phase was a Tween-80 aqueous solution with a mass concentration of 1%;

[0121] Dissolving polyethylene terephthalate in ethyl acetate, adding aluminum oxide nanoparticles with an average particle size of 50 nm, and stirring evenly to obtain a shell material suspension, wherein the concentration of polyethylene terephthalate in the shell material suspension is 8%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 35%;

[0122] The shell material suspension was added dropwise to the core material emulsion at a stirring speed of 8000 rpm. After the addition was completed, glutaraldehyde was added under stirring for cross-linking reaction. The mixture was then heated to 70°C and stirred for 3 hours. The mixture was filtered, washed and dried to obtain fire-extinguishing microcapsules. The volume ratio of the shell material suspension to the core material emulsion was 1:2.

[0123] The fire extinguishing agent consists only of fire extinguishing microcapsules.

[0124] Comparative Example 2

[0125] Silicon-based aerogel preparation:

[0126] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0127] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0128] Soak the gel in ethanol for 18 h, and repeat the above soaking steps 4 times;

[0129] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0130] The extinguishing agent consists solely of silicon-based aerogel.

[0131] Comparative Example 3

[0132] Silicon-based aerogel preparation:

[0133] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0134] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0135] The gel was immersed in an ethanol solution for 18 hours, wherein the ethanol solution was prepared by mixing a 10 wt % potassium carbonate aqueous solution with ethanol in a volume ratio of 1:2. The above immersion step was repeated 4 times;

[0136] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0137] The extinguishing agent consists only of aerogel particles.

[0138] Comparative Example 4

[0139] Silicon-based aerogel preparation:

[0140] Tetraethyloxysilane and ethanol were mixed and stirred at a mass ratio of 1:4, and then hydrochloric acid was added to adjust the pH value to 2.4. At the same time, water with a volume twice that of tetraethyloxysilane was added, and the mixture was stirred and reacted for 30 minutes to obtain a sol.

[0141] Ammonia water was added to the sol to adjust the pH value to 5.5, and the mixture was stirred for 20 h and allowed to stand at 40°C for 24 h to obtain a gel;

[0142] Soak the gel in ethanol for 18 h, and repeat the above soaking steps 4 times;

[0143] The gel after solvent replacement was immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state (31°C, 7.38MPa), and then the carbon dioxide was slowly released to complete drying to obtain aerogel. The aerogel was crushed to obtain aerogel particles with an average particle size of 50μm.

[0144] The fire extinguishing agent is obtained by mixing aerogel particles and potassium carbonate in a mass ratio of 1:1.

[0145] In order to further verify the fire extinguishing effect of the technical solution of the present application, the fire extinguishing agents prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0146] 1. Fire extinguishing efficiency test:

[0147] Prepare the fire source:

[0148] Class A fire source: wood;

[0149] Class B fire source: gasoline;

[0150] Lithium battery fire source: ternary battery pack;

[0151] Thermocouple temperature sensors are placed around the fire source to monitor the temperature changes around the center of the fire source.

[0152] Application of fire extinguishing agent: For Class A and Class B fire sources, apply fire extinguishing agent 10 seconds after the fire source initially burns, and test the flame extinguishing time. For lithium battery fire sources, apply fire extinguishing agent after the battery thermal runaway is triggered, and record the fire extinguishing time and heat source temperature change.

[0153] 2. High temperature resistance test:

[0154] Simulate a lithium battery fire scenario, initiate battery thermal runaway, and reach a fire source temperature of over 700°C. Apply the same amount of fire extinguishing agent after the fire source reaches 700°C, and test the working duration of the fire extinguishing agent and its stability at high temperatures. Observe the morphological changes of the fire extinguishing microcapsules and aerogel composites at high temperatures, and record the release rate of the fire extinguishing agent and whether the material ruptures or fails prematurely. Record the time the fire extinguishing agent remains effective in a high temperature environment (from application to failure or re-ignition of the fire source).

[0155] 3. Thermal insulation performance test:

[0156] The heat insulation effect of the fire extinguishing agents of each embodiment and comparative example was evaluated, especially the heat insulation capacity around the fire source. A high temperature fire source was simulated, and the temperature was set at 500-800°C, simulating a lithium battery fire or a Class B fire source. Multiple temperature sensors were arranged around the fire source, at a distance of 5cm, 10cm, 15cm, and 20cm from the fire source, respectively. After applying the fire extinguishing agent, the changes in the fire source and surrounding temperature were continuously monitored.

[0157] Adhesion and long-term effectiveness test:

[0158] Test the adhesion of the fire extinguishing agent on different surfaces (especially vertical surfaces and irregular surfaces) and the continuous working time of the fire extinguishing agent to evaluate the long-term fire extinguishing ability of the material.

[0159] The specific data results are shown in the following table:

[0160] project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Class A fire extinguishing time / s 16.3 17.5 15.2 25.6 13.8 13.6 13.3 Class B fire extinguishing time / s 20.1 21.4 19.3 30.5 17.2 16.9 15.7 Lithium battery fire extinguishing time / s 55.7 60.4 51.8 85.9 40.2 38.6 37.9 High temperature resistant effective working time / s 72.4 66.8 81.5 61.3 112.7 116.5 119.3 Temperature drop near the fire source (5cm) / ℃ 181.6 172.3 186.8 163.4 223.5 227.9 229.6 Temperature drop near the fire source (20cm) / ℃ 51.8 47.3 54.5 41.9 75.7 77.9 79.1 Adhesion / min 12.3 11.5 13.2 7.6 15.8 16.4 17.3 Long-acting / min 22.6 20.7 23.5 13.4 32.9 34.6 36.2

[0161] project Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Class A fire extinguishing time / s 35.8 32.7 33.4 31.6 Class B fire extinguishing time / s 40.4 36.2 37.8 35.9 Lithium battery fire extinguishing time / s 125.3 91.7 94.6 92.3 High temperature resistant effective working time / s 44.7 71.3 73.8 70.2 Temperature drop near the fire source (5cm) / ℃ 121.8 172.9 175.4 173.8 Temperature drop near the fire source (20cm) / ℃ 34.5 50.2 51.8 49.6 Adhesion / min 5.2 7.1 8.2 7.5 Long-acting / min 10.8 13.5 14.1 13.7

[0162] Fire extinguishing efficiency:

[0163] Example 5-7 (composite potassium carbonate aerogel): The fire extinguishing time for Class A fire source is 13.3-13.8 seconds, the fire extinguishing time for Class B fire source is 15.7-17.2 seconds, and the fire extinguishing time for lithium battery fire source is 37.9-40.2 seconds. The fire extinguishing efficiency of this group of materials is significantly higher than that of other examples.

[0164] Example 1-3: The fire extinguishing time for Class A fire source is 15.2-17.5 seconds, for Class B fire source is 19.3-21.4 seconds, and for lithium battery fire source is 51.8-60.4 seconds. Although electrostatic spraying improves uniformity, the fire extinguishing efficiency is slightly lower than that of the composite potassium carbonate material.

[0165] Example 4: Due to uneven mixing, the fire extinguishing time is relatively long, 25.6 seconds for Class A fire source, 30.5 seconds for Class B fire source, and 85.9 seconds for lithium battery fire source.

[0166] Comparative Example 1: Only microcapsules, the fire extinguishing efficiency is poor, 35.8 seconds for Class A fire source, 40.4 seconds for Class B fire source, and 125.3 seconds for lithium battery fire source.

[0167] Comparative Examples 2-4: Although aerogel is used for thermal insulation, the fire extinguishing effect is poor, with the fire extinguishing time for Class A fire source being 31.6-33.4 seconds, the fire extinguishing time for Class B fire source being 35.9-37.8 seconds, and the fire extinguishing time for lithium battery fire source being 91.7-94.6 seconds.

[0168] High temperature resistant new energy:

[0169] Example 5-7: The high temperature resistant working time is 112.7-119.3 seconds, which is very suitable for high temperature scenes such as lithium battery fire. The heat absorption property of composite potassium carbonate prolongs the working time.

[0170] Embodiment 1-3: The working time is 66.8-81.5 seconds, which is suitable for conventional fire sources and lithium battery fire sources, but slightly worse than compound potassium carbonate.

[0171] Example 4: The working time at high temperature was only 61.3 seconds due to conventional mixing.

[0172] Comparative Example 1: Failure is fast at high temperature, and the working time is only 44.7 seconds.

[0173] Comparative Examples 2-4: The aerogel provides a certain high temperature resistance, and the working time is 70.2-73.8 seconds.

[0174] Thermal insulation performance:

[0175] Example 5-7: Excellent performance, the temperature near the fire source dropped by 223.5-229.6°C, and the temperature far away dropped by 75.7-79.1°C. The potassium carbonate composite aerogel provides good thermal insulation and heat absorption capabilities.

[0176] Example 1-3: The temperature near the fire source dropped by 172.3-186.8°C, and the temperature far away dropped by 47.3-54.5°C, with good insulation effect.

[0177] Example 4: The heat insulation effect is slightly worse, the temperature near the fire source drops by 163.4°C, and the temperature far away drops by 41.9°C.

[0178] Comparative Example 1: Due to the absence of aerogel, the thermal insulation effect is poor, the temperature near the fire source only drops by 121.8°C, and the temperature far away drops by 34.5°C.

[0179] Comparative Example 2-4: The heat insulation effect is moderate, with the temperature near the fire source dropping by 170.2-175.4°C and the temperature far away dropping by 49.6-51.8°C.

[0180] Adhesion and long-term effect:

[0181] Example 5-7: The adhesion performance is the best, which can last for 15.8-17.3 minutes, and the long-term fire extinguishing ability can last for 32.9-36.2 minutes.

[0182] Example 1-3: The adhesion is good, lasting for 11.5-13.2 minutes, and the long-term effect is 20.7-23.5 minutes.

[0183] Example 4: Due to poor mixing effect, the adhesion was 7.6 minutes and the long-term effect was only 13.4 minutes.

[0184] Comparative Example 1: The adhesion and long-term effect are poor, which are 5.2 minutes and 10.8 minutes respectively.

[0185] Comparative Example 2-4: The adhesion is moderate, lasting for 7.1-8.2 minutes, and the long-term effect is 13.5-14.1 minutes.

[0186] In all tests, Examples 5-7 performed well, with fire extinguishing efficiency, high temperature resistance, heat insulation, adhesion and long-term effectiveness reaching the best level, and were particularly suitable for high temperature and complex fire scenes (such as lithium battery fires). Examples 1-3 performed well, especially in conventional Class A and Class B fire sources, with good fire extinguishing efficiency and adhesion.

[0187] In Example 4, the overall performance of the fire extinguishing agent is affected due to the uneven mixing method, and the effect is poor in a high temperature environment.

[0188] Comparative Example 1 lacks the thermal insulation effect of aerogel, and has poor fire extinguishing efficiency and high temperature resistance. Comparative Examples 2-4 have improved performance, but due to the lack of chemical fire extinguishing agents, the fire extinguishing efficiency is still not ideal.

[0189] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires, characterized in that: The fire extinguishing agent includes fire extinguishing microcapsules and aerogels.

2. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 1, characterized in that: The fire extinguishing microcapsule comprises a core material and a shell, wherein the core material is perfluorohexanone, and the shell material is polyethylene terephthalate modified with aluminum oxide nanoparticles.

3. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 1, characterized in that: The preparation method of the fire extinguishing microcapsule comprises: Core material preparation: perfluorohexanone is added dropwise to the stirred aqueous phase to form a core material emulsion with a mass concentration of 40%-50%, and the aqueous phase is a Tween-80 aqueous solution with a mass concentration of 0.5%-2.0%; Shell material preparation: dissolve polyethylene terephthalate in ethyl acetate, add aluminum oxide nanoparticles, and stir evenly to obtain a shell material suspension; Preparation of microcapsules: add the shell material suspension to the stirring core material emulsion, add glutaraldehyde to carry out cross-linking reaction, then heat to 60-80°C, keep stirring for 2-4 hours, filter, wash and dry to obtain fire-extinguishing microcapsules.

4. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 3, characterized in that: During the core material preparation, the stirring speed of the aqueous phase is 5000-10000 rpm.

5. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 3, characterized in that: The concentration of polyethylene terephthalate in the shell material suspension is 5%-10%, and the concentration of aluminum oxide nanoparticles in the shell material suspension is 30%-40%.

6. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 3, characterized in that: The volume ratio of the shell material suspension to the core material emulsion is 1:(1-3).

7. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 1, characterized in that: The aerogel is a silicon-based aerogel.

8. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 1, characterized in that: The preparation method of the aerogel comprises: Preparation of sol: After tetraethyloxysilane and ethanol are mixed and stirred evenly, hydrochloric acid is added to adjust the pH value to 2-3, and water is added at the same time, and the mixture is stirred and reacted for 20-40 minutes to obtain a sol; Gel preparation: Add ammonia water to the sol, adjust the pH value to 5-6, stir and react for 12-24 hours, and stand at 30-50°C for 24 hours to obtain a gel; Solvent replacement: Soak the gel in ethanol for 12-24 hours, and repeat the above soaking steps 3-5 times; Drying: The solvent-replaced gel is immersed in liquid carbon dioxide, heated and pressurized to make the liquid carbon dioxide reach a supercritical state, and then the carbon dioxide is slowly released to complete drying to obtain aerogel. The aerogel is crushed to obtain aerogel particles with an average particle size of 10-100μm.

9. The fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires as claimed in claim 1, characterized in that: The solvent replacement step further includes adding an aqueous solution of potassium carbonate to the ethanol.

10. The method for preparing a fire extinguishing agent for extinguishing Class A, Class B and lithium battery fires according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: Pour the dried aerogel powder into the hopper of the electrostatic spraying equipment, spray the aerogel powder onto the surface of the fire extinguishing microcapsules at an electrostatic voltage of 50-70 kV and an air pressure of 0.1-0.3 MPa, with a spraying distance of 15-30 cm and a spraying time of 3-5 s; Step 2: After spraying, the composite material obtained after spraying is dried at 40-60° C. for 12-24 hours to obtain a fire extinguishing agent.

Citation Information

Patent Citations

  • Preparation method of perfluorohexanone microcapsule

    CN115487459A

  • Lithium battery composite fire extinguishing agent and preparation method and application thereof

    CN116059574A

  • Efficient aerogel fire extinguishing agent and preparation method thereof

    CN116785637A

  • Solid aerogel perfluorohexanone fire extinguishing sheet and preparation method thereof, magnetic attraction fire extinguishing patch and energy storage device

    CN116850522A

  • Preparation method of silicon oxide aerogel nanopowder and fingerprint display application of silicon oxide aerogel nanopowder

    CN117843001A